QUALITY AND ACCEPTANCE IN TECHNOLOGY PROJECTS: PROPOSAL FOR A CUSTOMER-ORIENTED GOVERNANCE FRAMEWORK - Lunardeli, Stella (Revista Gênero e Interdisciplinaridade, 2026)
Technology project management, especially in the agile context, requires continuous alignment between the technical quality of the delivery and customer satisfaction. This article presents a Systematic Literature Review (SLR) focused on the convergence of governance and quality standards, such as the PMBOK 7th Edition, the Scrum Guide, and ISO 9001, with the aim of proposing a Customer-Oriented Quality Governance Framework (FGQ-OC). The research, based on literature from the last five years (2020-2025), demonstrates that customer acceptance is the central criterion for project success, surpassing mere compliance with the initial scope. The proposed FGQ-OC aims to provide a robust structure for digital corporate environments, ensuring that technical requirements and customer expectations are integrated from conception to final delivery. Expected results include the definition of measurable acceptance indicators, which can be applied to enhance governance and the management of value in technology projects.